2023
DOI: 10.31234/osf.io/cxaw7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptability and perceived harm of calorie labelling and other obesity policies: a cross-sectional survey study of UK adults with eating disorders and other mental health conditions

Abstract: Objective: We assessed perceptions of recently proposed UK obesity-related public health policies (mandatory calorie labelling, banning of advertisements of unhealthy food and drinks online and before 9 pm on TV, and banning “buy one get one free” deals for unhealthy food and drinks) in people with an eating disorder (ED) and other mental health conditions. Method: 1,273 participants with a self-reported mental health condition (N=583 with an ED) completed an online survey in September – November 2022. Multino… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…There has been some public concern about the implementation of mandatory kcal labelling in England, 39 specifically about the potential negative impacts on people with eating disorders. 42 In an attempt to mitigate potential negative impacts, as part of government guidance for kcal labelling, it was recommended that kcal-free menus be available in outlets on request. Our results found that only 12% of outlets implementing kcal labelling were able to provide researchers with a kcal-free menu when requested in-store.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some public concern about the implementation of mandatory kcal labelling in England, 39 specifically about the potential negative impacts on people with eating disorders. 42 In an attempt to mitigate potential negative impacts, as part of government guidance for kcal labelling, it was recommended that kcal-free menus be available in outlets on request. Our results found that only 12% of outlets implementing kcal labelling were able to provide researchers with a kcal-free menu when requested in-store.…”
Section: Discussionmentioning
confidence: 99%